Indications for Open Reduction Internal Fixation of Anterior Pelvic Ring Disruptions. (September 2018) - Wright, Raymond D.
Abstract : Summary: In acute trauma, pelvic ring instability can lead to hemorrhage and hemodynamic instability. Pelvic ring instability and displacement that is not stabilized may lead to chronic pain, sitting imbalance, and limb length inequality. Methods and timing of securing anterior pelvic ring injuries operatively is controversial and debatable. Many orthopaedic trauma surgeons would agree that acceptable methods to treat a disrupted anterior pelvic ring fracture include nonoperative care, external fixation, internal spanning fixators, intramedullary superior ramus screws, and open reduction internal fixation. We will review the indications for open reduction internal fixation fractures and disruptions of the anterior pelvic ring.